Translation, Language, Anthropology: Notes from the Field. Issue 1 (2nd January 2016) - Kothari, Rita
Abstract : This essay, in addition to being a reflection on field notes, is about the non-representability of translation. It illustrates the simultaneous possibilities of closure and openness in translation, acts that seal borders, and those that open up new voices. It shows that translation also creates equivalent categories. In doing so, translators align themselves with the dominant codes of classification. These observations have been drawn from ethnographic fieldwork in a remote part of rural India. The essay also shows how fieldwork offers a site of interplay involving both language and ethnography, making the discussion of one in isolation from the other a futile exercise. It extends the idea of 'difference' upon which translation studies is predicated. If by 'difference' we understand a text, a culture and a context other than those the translator/ethnographer brings with them, the essay shows the dangers of presumed sameness.